Die Kontrolle nationaler Regionalbeihilfen in der Europäischen Union - Karl, Helmut (Raumforschung und Raumordnung | Spatial Research and Planning, 2002)
Controls at EU level of the provision of regional development aid within Member States represent a key task of European integration. However, the goals pursued by the Commission in undertaking such controls relate to both economic competitiveness and to regional policy. Consequently, the Commission has to accept on regional-policy grounds that competitiveness within the European single market will be distorted as a result of commercially based investment grants, even though this disadvantage of regional aid could be avoided through the use of infrastructure grants. Moreover, EU controls of national development aid force regional policy at national level to adopt the model of European cohesion policy and thus enhance the position of the EU as the provider of its own grants to support regional policy.
Keywords: Article